Tin(IV) compounds of tridentate thiosemicarbazone Schiff bases: synthesis, characterization, in-silico analysis and in vitro cytotoxicity - Enis Nadia Md Yusof,; Alister, J.; Sakoff, Jennette A; Simone, Michela I; Veerakumarasivam, Abhi *; Tiekink, Edward R. T. *; Ravoof, Thahira Begum S. A. (Elsevier, 2020)
Twelve tin(IV) compounds ( 5 - 16 ) derived from four tridentate thiosemicarbazone Schiff bases of 4-methyl-3-thiosemicarbazide with 2-hydroxy-3-methoxybenzaldehyde ( 1, 2 ) and 4-phenyl-3-thiosemicarbazide with 2,3-dihydroxybenzaldehyde ( 3, 4 ) of general formulae of [R 2 Sn(L n )] and [Sn(L n ) 2 ] (where R = Ph or Me; L n = 1 , 2 , 3 and 4 ) were synthesized and characterized by elemental analysis, IR, UVvis, mass spectrometry and multinuclear NMR ( 1 H, 13 C and 119 Sn) spectroscopy. X-ray crystallographic data was obtained for 11′ , a 2:1 co-crystal between Ph 2 Sn(L 2 ) ( 11 ) and 3-methoxysalicylaldehyde azine, and Me 2 Sn(L 2 ) ( 12 ); L 2 H 2 is 2-(2-hydroxy-3-methoxybenzylidene)-Nphenylhydrazinecarbothioamide. The analysis revealed distinct coordination geometries with 11 and 12 approaching trigonal-bipyramidal. In the crystal of 11′ , supramolecular dimers arising from amine-N–H … S(thiolate) hydrogen bonding and {… HNCS} 2 synthons are evident; π(chelate ring) … π(oxidobenzylidene) stacking is also apparent. In the crystal of 12 , supramolecular, helical chains are generated by a combination of amine-N–H … O(phenoxide) hydrogen bonding and Sn … S secondary bonding. The cytotoxic activity of the compounds against a panel of ten cancer cell lines, [HT29 (colon), U87 and SJ-G2 (glioblastoma), MCF-7 (breast), A2780 (ovarian), H460 (lung), A431 (skin), DU145 (prostate), BE2-C (neuroblastoma), and MIA (pancreas) and one normal cell line, MCF-10A (normal breast)] were investigated. The thiosemicarbazone Schiff bases 1 and 4 as well as the diphenyltin(IV) compounds showed a strong ability to inhibit the growth of cancer cells, with particular selectivity against HT29, MCF-7, A2780, A431, BE2-C, SJ-G2, and MIA cell lines. The structure-activity relationship of all these compounds were studied by evaluating the effect of alkyl and aryl groups attached at the thiosemicarbazone backbone, the methoxy/hydroxyl groups present at the meta -position of the phenyl ring and alkyl or aryl groups bound to the tin center.